Child care subsidy generosity and child maltreatment: the moderating effects of administrative burden - Thibodeau, Eric L. (Journal of family violence, 2026)
Purpose: Child maltreatment (CM) (i.e., neglect, emotional abuse, physical abuse, and/or sexual abuse) has profound and wide-ranging impacts on child development. A significant body of literature demonstrates robust links between poverty/financial hardship and risk for CM. The Childcare and Development Fund (CCDF) is the primary federal program which subsidizes child care costs for families, with children under age 13 (under age 19 for special needs), in the United States with lower-incomes. States have considerable discretion in determining policy options which can greatly impact both the generosity and adminstrative burden of the program. Methods: At the state-level, using a moderated, two-way, fixed-effect approach, we investigate the association between the generosity of CCDF policies (e.g., copayment size, enrollment income, work requirements, etc.) and rates of child maltreatment investigations and substantiations involving children under the age of five. Furthermore, we examine how the effect of the generosity of child care subsidies on child maltreatment depends on the level of administrative burden (i.e., income cliffs and redetermination periods). Results: In general, as subsidy generosity increases, rates of child maltreatment investigations and substantiations decrease, and these associations are strengthened when administrative burden is reduced. Conclusions: Administrative burdens may diminish the impact that subsidies have on reducing family stress and financial hardship therefore reducing the potential preventive effect subsidies have on abuse and neglect of children, especially those most vulnerable-young children.